Solar-Wind Structures That Are Not Destroyed by the Action of Solar-Wind Turbulence - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2021)
If MHD turbulence is a dominant process acting in the solar wind between the Sun and 1 AU, then the destruction and regeneration of structure in the solar-wind plasma is expected. Six types of solar-wind structure at 1 AU that are not destroyed by turbulence are examined: (1) corotating-interaction-region stream interfaces, (2) periodic density structures, (3) magnetic structure anisotropy, (4) ion-composition boundaries and their co-located current sheets, (5) strahl-intensity boundaries and their co-located current sheets, and (6) non-evolving Alfvénic magnetic structure. Implications for the solar wind and for turbulence in the solar wind are highlighted and a call for critical future solar-wind measurements is given.